MAXIMS OF THE CATEGORY OF POLITENESS IN ENGLISH FICTION (In the example of S. Chboskyʼs work "The Perks of being a wallflower") (Scientific journal of the Fergana State University, 2024)
Based on J. Leechʼs teaching, maxims of politeness category were analyzed on the basis of English literary text. According to the teaching, descriptive qualitative method was used in axiolinguistic analysis of each politeness maxims and classification stages. The axiological level of using the category of politeness in the speech of English-speaking peoples was shown through examples from the work of the English writer Steven Chbosky, "The Perks of being a wallflower", and it was determined that speakers with introverted behavior are of great importance in the English value.